2005
DOI: 10.1677/joe.1.06096
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone export from cells: contribution of P-glycoprotein

Abstract: Verapamil inhibits tri-iodothyronine (T 3 ) efflux from several cell types, suggesting the involvement of multidrug resistance-associated (MDR) proteins in T 3 transport. The direct involvement of P-glycoprotein (P-gp) has not, however, been investigated. We compared the transport of compared with MDCKII cells, probably reflecting enhanced export of T 3 from MDCKII-MDR cells rather than reduced cellular uptake, as P-gp typically exports substances from cells. Verapamil lowered the rate of 125 I-T 3 efflux from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 27 publications
0
26
0
2
Order By: Relevance
“…TIM was previously characterized to be an inhibitor of several mammalian efflux pumps (25,26,31,32) and enhanced the potency of antibiotics against Gram-positive bacteria in broth cultures (15). The importance of evaluating efflux inhibitors in multiple relevant disease models is represented by the work in this study, where different efflux inhibitor-antibiotic combinations had different effects on mycobacterial growth in MIC assays, infected macrophage assays, and mouse infections.…”
Section: Discussionmentioning
confidence: 94%
“…TIM was previously characterized to be an inhibitor of several mammalian efflux pumps (25,26,31,32) and enhanced the potency of antibiotics against Gram-positive bacteria in broth cultures (15). The importance of evaluating efflux inhibitors in multiple relevant disease models is represented by the work in this study, where different efflux inhibitor-antibiotic combinations had different effects on mycobacterial growth in MIC assays, infected macrophage assays, and mouse infections.…”
Section: Discussionmentioning
confidence: 94%
“…3c) and suggested that tetrac may act as an inhibitor of P-gp activity. In light of the previous observation that thyroid hormones are able to bind to avb3 integrin [8] and to P-gp [28], the finding that tetrac inhibits their binding to integrins raises the possibility that tetrac may also interfere with their binding to Pgp. Using the same logic, tetrac may also compete with drugs for the binding to P-gp and thus, disrupt the efficacy of this transporter.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent biotransformation reactions are catalyzed by UGTs and SULTs. Conjugated and unconjugated molecules are then excreted into bile via transporters localized on the canalicular membranes such as multidrug resistance-associated proteins (44,67). It will therefore be of interest to determine the extent to which canalicular transport of THs and other hormones is regulated by fasting and cAMP.…”
Section: Discussionmentioning
confidence: 99%